10B/11B isotopic ratio and atomic composition of boron carbide: Determination by proton induced γ-ray emission and proton elastic backscattering spectrometry. (October 2017) - Sunitha, Y.; Kumar, Sanjiv
Abstract: The 10 B/ 11 B isotopic ratio and the atomic composition of boron carbide, an important non-metallic ceramic, have been determined non-destructively by the particle induced γ-ray emission (PIGE) and elastic backscattering spectrometry (EBS) techniques with proton beams. The analysis has been performed on powder as well as sintered ceramics containing boron in natural or 10 B enriched composition. The PIGE technique, performed at a 4.0–4.2 MeV proton energy, utilizes the 10 B(p, αγ) 7 Be, 10 B(p, p′γ) 10 B and 11 B(p, p′γ) 11 B nuclear reactions for (a) the isotopic analysis of boron and (b) the determination of total boron, and the 13 C(p, p′γ) 13 C nuclear reaction for the determination of carbon. The irradiation conditions were optimized by determining the thick targets yields of prompt γ-rays, characteristic of these reactions, in the 3.0–4.2 MeV proton energy range. The quantitative analysis was performed by comparison with standards taking into account the attenuation of γ-rays in the specimens. The uncertainty in the determination of the 10 B/ 11 B isotopic ratio and the B/C atomic ratio is about 2% and about 5% respectively. The analysis by EBS, on the other hand, involves the 10 B(p, p) 10 B, 11 B(p, p) 11 B and 12 C(p, p) 12 C elastic scatterings at the 2.0 MeV proton energy. This method too yields satisfactory results. Between the two, PIGE is the method of choice for bulk analysis while EBS is useful in discerning compositional variations in surface regions. Graphical abstract: Highlights: 10 B/ 11 B and B/C ratios in boron carbide ceramics are determined non-destructively. The methods are particle induced γ-ray emission and elastic backscattering spectrometry with protons. Powder and also sintered ceramics are analyzed. Accurate and precise results are obtained. Relative qualitative density of sintered ceramics can be obtained.